2016
DOI: 10.1080/08820538.2016.1188127
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Corneal Parameters in Patients with Constitutional Thinness Using Scheimpflug Imaging

Abstract: Corneal thicknesses were significantly thinner in CT subjects compared to those in control subjects. The impact of constitutional thinness on corneal parameters should be further investigated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(24 citation statements)
references
References 19 publications
0
24
0
Order By: Relevance
“…Of the thirty-five studies selected in the systematic review, twenty-six (7)(8)(9)(10)(11)16,17,(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)32,33,36,37,40,41,43,45,46) enrolled females exclusively, three (18,34,39) enrolled males exclusively and six (30,31,35,38,42,44) enrolled both females and males (Table 1). Of these thirty-five studies, thirty-two (7)(8)(9)(10)(11)(16)(17)(18)(19)(20)(21)(22)(23)(24)…”
Section: Population Characteristicsmentioning
confidence: 99%
See 4 more Smart Citations
“…Of the thirty-five studies selected in the systematic review, twenty-six (7)(8)(9)(10)(11)16,17,(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)32,33,36,37,40,41,43,45,46) enrolled females exclusively, three (18,34,39) enrolled males exclusively and six (30,31,35,38,42,44) enrolled both females and males (Table 1). Of these thirty-five studies, thirty-two (7)(8)(9)(10)(11)(16)(17)(18)(19)(20)(21)(22)(23)(24)…”
Section: Population Characteristicsmentioning
confidence: 99%
“…Weight history was considered in twenty-five (7-10,16-19,21-23, 27,28,30,31,35-39,41-44,46) of the thirty-five studies: four studies (16,38,43,46) reported a stable body weight for a certain period of time before the experiment (ranging from 1 week (38) to 2 years (16,43,46) ), and twenty-one studies (7)(8)(9)(10)(17)(18)(19)(21)(22)(23)27,28,30,31,(35)(36)(37)39,41,42,44) reported it for a longer period throughout the growth period and/or the post-pubertal period. Weight history was not considered in the ten (11,20,(24)(25)(26)(32)(33)(34)40,45) remaining studies.…”
Section: Diagnosis Of Constitutional Thinnessmentioning
confidence: 99%
See 3 more Smart Citations